2015
DOI: 10.1111/tbed.12393
|View full text |Cite
|
Sign up to set email alerts
|

A Case-control Study of Haemorrhagic Septicaemia in Buffaloes and Cattle in Karachi, Pakistan, in 2012

Abstract: Summary A retrospective epidemiological case–control study was performed in Karachi, Pakistan, from January to April 2013. The owners of 217 dairy cattle and buffalo farms from six different locations in Karachi were interviewed. The aim of the study was to identify risk factors associated with the presence of haemorrhagic septicaemia (HS). Farms with a history of at least one instance of sudden death in a dairy animal during 2012 and a positive clinical HS diagnosis (made by local veterinarians) were defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The disease is associated with a specific serotype of Pasteurella multocida (Kuranasree, 2016) and is particularly important in Southeast Asian countries including Malaysia (Jesse et al, 2013;Chung et al, 2015). Buffaloes are more susceptible than cattle and the disease is usually observed more frequently following poor husbandry conditions in countries with disease surveillance that is not well developed (Annas et al, 2014;Moustafa et al, 2017). Similarly, in Malaysia, the mortality rate was higher among buffaloes compared to cattle despite the fact that the buffalo population in Malaysia was half that of cattle (Rafidah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is associated with a specific serotype of Pasteurella multocida (Kuranasree, 2016) and is particularly important in Southeast Asian countries including Malaysia (Jesse et al, 2013;Chung et al, 2015). Buffaloes are more susceptible than cattle and the disease is usually observed more frequently following poor husbandry conditions in countries with disease surveillance that is not well developed (Annas et al, 2014;Moustafa et al, 2017). Similarly, in Malaysia, the mortality rate was higher among buffaloes compared to cattle despite the fact that the buffalo population in Malaysia was half that of cattle (Rafidah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors did not have an individual history of the animals, such as previous diseased experience or previous medication, but most of the herds had experiences of sudden death in cows with undifferentiated respiratory diseases. Most of the farms in this study were supplied by underground water, while a study in Pakistan has demonstrated that supplying underground water on farms increased the risk of outbreaks by 2.9 [28]. It has been discussed that rice paddy crop cultivation may favor the disease outbreaks, whereas the dairy farms in our study were surrounded by rice paddy fields, and buffaloes were pastured in the fields after harvest [29].…”
Section: Discussionmentioning
confidence: 75%
“…This might be spreading the pathogen across the farms. Moreover, Thailand is an endemic area for foot and mouth disease, and a previous study has suggested that the disease increases the risk of HS outbreaks by 2.37 [28]. Although HS is a highly fatal disease, the severity of clinical signs, morbidity, and mortality in dairy cows is lesser than in buffaloes.…”
Section: Discussionmentioning
confidence: 99%
“…One out of four buffalo or cows were found suffering from misstates (Ferrari et al, 2014). Moustafa et al (2017) reported 58.7% of the animals' deaths due to five endemic diseases like HS, FMD, rinderpest, anthrax and blackleg. Previously due to five economical endemic diseases, 58.7% of deaths were reported.…”
Section: Introductionmentioning
confidence: 99%